Challenging Legislative Infringements of the Inherent Aboriginal Right of Self-Government - McNeil, Kent (Osgoode Digital Commons, 2003)
The Parliament of Canada exercised its s.91 (24) legislative authority over "Indians, and Lands reserved for the Indians" when it enacted the Indian Act in 1816. Through this Act and its precursors, the Canadian government imposed the band governance system on First Nations. Although traditional forms of Aboriginal government were not abolished by the imposition of this system, there can be no doubt that the capacity of Aboriginal governments was impaired and the inherent right of self-government of at least some First Nations was infringed. After the enactment of section 35 of the Constitution Act, 1982, this infringement of the inherent right of self-government would have to be justified by the federal government in order to be valid. Moreover, any post-section 35(1) amendments to the band governance provisions would have to be justified to the extent that they amounted to further infringements of the inherent right. This would include, for example, the changes that were proposed in the now defunct First Nations Governance Act. Any First Nation that is subject to the Indian Act's band governance provisions could challenge the application of those provisions to it as an infringement of that First Nation's inherent right. The initial burden would be on the First Nation to prove its right of self-government and to show a prima facie infringement of that right by the Indian Act. Extinguishment aside, the burden would then be on the Crown to prove justification by establishing a valid legislative objective and respect for the Crown fiduciary obligations. If the Crown failed to do so, then the provisions of the Act that infringe that First Nation's inherent right of self-government would be inapplicable to it.